The Role of Fresh Start Mindset (FSM) and Collectivistic Orientation in Mental Health Promotion Messages - Lee, Yoon-Joo; Yoon, Hye Jin; Seo, Hae Yeon (Journal of current issues and research in advertising, 2025)
Promoting mental health issues faces significant barriers, especially due to ingrained societal norms and individuals' concerns about societal perceptions. This study, based on experimental design, explores the potential effectiveness of fresh start mindset (FSM) framing in enhancing perceived advertisement effectiveness and attitudes toward mental health issues, particularly among individuals with high collectivistic tendencies. This study uniquely suggests that mental health campaigns employing FSM framing may aid those with a strong collectivistic orientation to shift from viewing mental health as a source of societal stigma and nonconformity to embracing it as an opportunity for a fresh start. Additionally, this study highlights that an individual's attitude toward the issue functions as a mediating mechanism in assessing the responses to a mental health PSA using FSM framing.